The Analysis of Creative Content Virality in Jawa Pos-Radar Lawu Digital Media in the Era of Technology, Information, and Communication - Nur Wahyudin, Sapta Arif; Sutejo, Sutejo; Setiawan, Agus (ETTISAL : Journal of Communication, 2024)
Jawa Pos-Radar Lawu is part of the Jawa Pos Group which is oriented towards presenting important, interesting, and up-to-date information from various regions around Mount Lawu. Despite being less than a year old, this media outlet is dedicated to producing creative content through digital platforms. This is reflected in the diverse topics chosen periodically, which are based on their potential to be viral. This study aims to examine the virality of creative content on Jawa Pos-Radar Lawu’s digital media as a strategic approach to public communication in the context of the information and communication technology revolution. The researcher formulated two main research questions: (1) What factors contribute to the virality of content on Jawa Pos-Radar Lawu’s digital media? This study employs a qualitative approach, with the researcher serving as the primary instrument for data collection.  The research involves gathering data from the following sources: (1) content documents with the highest visitor numbers, (2) visitor statistics from March, April, and May, (3) recorded interviews with key informants, and (4) direct observation of Jawa Pos-Radar Lawu’s digital media. The data analysis process includes three stages: data reduction, data presentation, and drawing conclusions.  The findings indicate that the virality factors exhibited by Jawa Pos-Radar Lawu align with Berger's six theories of contagion: social currency, trigger, emotion, public, practical value, and story. The most dominant principles used are trigger, emotion and story.